Current Understanding of Parkinson's Disease (Eurasian Medical Research Periodical, 2023)
Patients with Parkinson's disease (PD) usually suffer from a wide range of non-motor manifestations of the disease, such as cognitive and affective disorders, fatigue, pain and various autonomic disorders, among which upper and lower gastrointestinal (GI) dysfunction plays a major role. These symptoms impair patients' ability to carry out daily activities and independence from others, and certainly have a negative impact on their quality of life.